Led by the Spirit: Missional Communities and the Quakers on communal vocation discernment - Love, Curtis R. (HTS teologiese studies, 2014)
This article argues that the term missional is an expression of the global shift towards a theocentric (rather than ecclesiocentric) understanding of mission. A Missional Community is a concrete, local embodiment of this missional ecclesiology and it comes to be through discerning its particular and ongoing vocation in the cosmic missio Dei. It is for this reason that we argued that communal vocation discernment lies at the heart of the Missional Community’s life and practice. This practice births, energises and renews the Missional Community in the wake of the boundary-breaking Spirit’s work in the local neighbourhood or context. Because communal vocation discernment is central to Missional Communities it seemed prudent to ask which other communities or traditions see discernment as central to their life and practice. In Western Christianity, the Quakers stand out as a significant example of communal discernment as their normal way of making decisions. We sought to answer whether the Quaker practice of communal discernment, in the Meeting for Worship in which Business is Conducted, is a suitable model for communal vocation discernment in Missional Communities. We suggested that it was not suitable in so far as it did not express an explicit commitment to being grounded and connected to a place or neighbourhood as a prerequisite for discernment. We suggested that it was suitable in so far as it continually reminds the community that communal discernment is not simply about making decisions or finding your vocation but at its heart is an act of worship. This awareness in the Quakers is primarily achieved through naming communal discernment spaces as worship spaces and through the strategic use of silence. We also suggested that the Quaker commitment to unity anddissent creates space for belonging, agency and responsibility in the community and that this is something which Missional Communities would do well to appropriate in their own communal vocation discernment.